Adaptive power control for terrestrial microwave communication link in tropical region - Abdul Rahman, Tharek; Toh, Chee Leng (2001)
Propagation of microwave signal above lOGHz involves not only free space path loss but also other attenuation due to atmospheric phenomena. In tropical region, the high rain rate has become a serious degradation factor for microwave communication system. Rain attenuation reduces the receiving signal in microwave link, thus decrease the signal-to-noise ratio (SNR) and increase the bit-error-rate (HER). Adaptive power control is proposed as a solution for maintaining the received signal above the threshold level corresponding to the BER. This paper presents the system level design of a 26GHz microwave communication transceiver with adaptive power control to overcome the rain attenuation problem. The transceiver system design and simulation are done with communication system design software.